Assessing the association between age at first sexual intercourse and migraine: a Mendelian randomization study - Zhu, Guoliang; Wang, Miao; Wang, Yawen; Kong, Fanyi (Frontiers in Neurology, 2024)
Background and objectives As indicated by observational and genetic variation studies, age at first sexual intercourse (AFS) may be associated with migraine attack, but there is a lack of evidence from real-world studies due to ethical concerns. Therefore, we conducted a Mendelian randomization study to determine the causal relationship between AFS and migraine. Methods We extracted instrumental variables from summary data of a genome-wide association study (GWAS) on AFS and migraine and then conducted two-sample Mendelian randomization analyses. GWAS data for AFS and migraine were obtained from 397,338 unrelated individuals (214,547 females and 182,791 males) and 306,314 individuals (18,477 patients and 287,837 control individuals), respectively. Results There was a causal relationship between AFS and risk for migraine (odds ratio (OR) = 0.73, 95% confidence interval (CI) [0.61 to 0.86]), both for migraine with aura (MWA; OR = 0.72, 95% CI [0.58 to 0.89]) and migraine without aura (MOA; OR = 0.66, 95% CI [0.51 to 0.86]). Stratified analyses provided suggestive evidence of the causal relationship between delayed AFS and a decreased risk of migraine for both males (OR = 0.71, 95% CI [0.59 to 0.84]) and females (OR = 0.73, 95% CI [0.61 to 0.89]). Reverse Mendelian randomization did not reveal any effect of migraine on AFS (p > 0.05). No pleiotropy was detected. Discussion A delayed AFS is a protective factor against migraine (for both MWA and MOA) in both males and females. This causal relationship indicates the presence of extracranial regulatory pathways of migraine.